2018
DOI: 10.1002/adma.201805353
|View full text |Cite
|
Sign up to set email alerts
|

Induced Formation of Structural Domain Walls and Their Confinement on Phase Dynamics in Strained Manganite Thin Films

Abstract: Domain walls (DWs) in strongly correlated materials have provided fertile ground for the discovery of exotic phenomena, and controlling the formation of DWs is still a challenge. Here, it is demonstrated that a new type of structural DW can be induced in a series of manganite thin films, which are engineered to achieve a robust charge‐ordering insulating (COI) ground state by selecting various films and substrates. The monoclinic domains are somewhat irregular in shape, and the corresponding DWs, taking the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Unless otherwise specified, the samples used in present work are 24 nm-thick hereafter (details for other film thicknesses are shown in the Supporting Information). Although LCMO/NGO(010) and (110) films still display a bulklike FMM state, an emergent COI phase is found in LCMO/NGO(100) and (001) films, which show clear signatures of phase separation (PS) and a complex phase evolution with temperature ( T ) and magnetic field ( H ). ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless otherwise specified, the samples used in present work are 24 nm-thick hereafter (details for other film thicknesses are shown in the Supporting Information). Although LCMO/NGO(010) and (110) films still display a bulklike FMM state, an emergent COI phase is found in LCMO/NGO(100) and (001) films, which show clear signatures of phase separation (PS) and a complex phase evolution with temperature ( T ) and magnetic field ( H ). ,, …”
Section: Resultsmentioning
confidence: 99%
“…Bulk LCMO exhibits a complex energy landscape with COI and FMM phases that are close in energy; , thus, one expects that any given set of external conditions can be used to favor one phase over the other. We have previously reported that an anisotropically strained LCMO film can generate a unique metastable electronic phase separation, even a highly robust COI state, from the bulklike FMM ground state, , which should be a good platform for examining the uniaxial strain effect. It is believed that the two in-plane orthogonal strains act to stabilize the COI phase, however, which one is dominant, the role played by each axis, and the correlation between intrinsic structural distortions and magnetic (and electric transport) responses remain unclear.…”
mentioning
confidence: 99%
“…Then, structural domain walls form between the monoclinic configurations and serve as the nucleation sites of the FMM phase instead of the COO phase, weakening the robustness of the COO phase. 30,32,34 At 50 K, the domain evolution of the same area is imaged, and the corresponding surface morphology is shown in Figure 5a. Due to a strong correlation between the local strain state and the magnetic or electronic properties, 41,42 the FMM phase gradually nucleates, grows, and connects at structural domain walls (Figures 5b−j and S7), and the percolation of the FMM phase occurs.…”
Section: Resultsmentioning
confidence: 99%
“…However, when the film enters into a COO state below T N , the domain periodicity may change. ,, Upon increasing the film thickness, structural domains and domain walls appear, and the induced structural inhomogeneity will alter the phase competition between these phases. Then, structural domain walls form between the monoclinic configurations and serve as the nucleation sites of the FMM phase instead of the COO phase, weakening the robustness of the COO phase. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation